Milestones in village history : a series of six radio talks - Young, Allan (Free Press GeorgetownGY, 2007)
Highlights important features in the history of the villages of Guyana. Emphasizes that the system of local government is not an arm or agent of the Central Government but an essential part of the democratic system of government.